Dietary Changes Among Normal and High Blood Pressure Adolescents During the COVID-19 Pandemic - Victoria, Bernadette; Sartika, Ratu Ayu Dewi; Putri, Rizti Millva (UI Scholars Hub, 2023)
The COVID-19 pandemic has significantly impacted adolescents' unhealthy eating habits and sedentary lifestyles, leading to an increase in blood pressure and obesity rate. High blood pressure among adolescents is an early indicator of adult hypertension, but this condition has received less attention recently. Therefore, this study aimed to determine the differences in dietary changes among high school students with normal and high blood pressure before and during the COVID-19 pandemic in West Lampung District, Indonesia. A cross-sectional design was used, and the sample population consisted of 167 students aged 14-19 years. The results showed that 43 participants had elevated blood pressure and stage 1 hypertension, accounting for 25.7% of the total population. Among these participants, 14 (32.6%) were found to be overweight and obese. Based on the results, students with high blood pressure were less likely to improve their dietary choices during the COVID-19 pandemic than those with normal blood pressure.